(untitled) (Research, Society and Development, 2022)
Abstract Introduction: Antimicrobial resistance is when the microorganism resists drug action, causing therapeutic ineffectiveness to the expected treatment. Objective: To verify aspects related to the prevention of antimicrobial resistance in the hospital unit. Methodology: This is a systematic review, adopting the method of integrative literature review delimited with studies published in the last 10 years on bacterial resistance against antibiotics. The search was carried out between October 2016 and January 2021. The inclusion criteria used for the adhesion of articles were articles published in the last 10 years, articles in Portuguese and English, articles scientifically published in journals and scientific databases whose study used bacterial resistance as a central focus. Results and Discussions: Of the 765 studies identified, 10 were selected for review. The strategies found are the Stewardship Antimicrobial Program (ASP), hand hygiene protocols, participation of the multidisciplinary team in continuing education, they serve to reduce microbial resistance in the hospital environment to antibiotics reducing length of stay, reducing cost and improving patient safety. Conclusions: In order to minimize the incidence of drug-resistant microorganisms and reduce costs, every strategy is valid within legal parameters, always based on scientific evidence.